2015
DOI: 10.1038/nature14320
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus toxoid and CCL3 improve dendritic cell vaccines in mice and glioblastoma patients

Abstract: Reprints and permissions information is available at www.nature.com/reprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
397
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(420 citation statements)
references
References 26 publications
8
397
0
Order By: Relevance
“…Finally, we looked at a number of inflammatory chemokines and chemokine receptors that are crucial for DC and T-cell recruitment to tumors. 2730 CCR5, CCL4, and CXCR3 were highly expressed in HPV+ HNSCC compared to HPV- tumors and normal samples, while CCL3 expression was elevated in HPV+ HNSCC compared to normal samples (Supplementary Figure 3). Overall, these results indicate a higher level of DC involvement in HPV+ than in HPV- HNSCC, with higher levels of effector cytokines that could be responsible for the elevated levels of T-cell infiltration of these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we looked at a number of inflammatory chemokines and chemokine receptors that are crucial for DC and T-cell recruitment to tumors. 2730 CCR5, CCL4, and CXCR3 were highly expressed in HPV+ HNSCC compared to HPV- tumors and normal samples, while CCL3 expression was elevated in HPV+ HNSCC compared to normal samples (Supplementary Figure 3). Overall, these results indicate a higher level of DC involvement in HPV+ than in HPV- HNSCC, with higher levels of effector cytokines that could be responsible for the elevated levels of T-cell infiltration of these samples.…”
Section: Resultsmentioning
confidence: 99%
“…In a clinical trial, GBM patients were randomized to receive standard therapy with pp65 DC vaccine alone or pp65 DC vaccine combined with a tetanus diphtheria toxoid (Td) booster vaccine. 57 The group that received the combination vaccination had significantly more DCs migrate to the draining lymph nodes due to an upregulation of CCL3. This increased migration correlated with significant improvement in overall survival (> 36.6 months versus 18.5 months).…”
Section: As Immunotherapeutic Targetmentioning
confidence: 97%
“…Mitchell and group reported results of a randomized trial for adults with newly diagnosed glioblastoma who were treated with DC vaccine loaded with Cytomegalovirus phosphoprotein 65 (pp65) with or without pre-treatment with tetanus toxoid (Td). 50 They found that pretreated patients had increased migration of DC to vaccine draining lymph nodes as well as increased interferon-g production in post-vaccine ELISPOT assays. In addition, they showed significantly improved progression free survival, with 3 patients alive and disease free at 3 y post-vaccine.…”
Section: Adjuvant For DC Vaccinesmentioning
confidence: 99%
“…Other recently published work has focused on the use of novel adjuvants from natural sources, [46][47][48][49] known recall antigens, 50 tumor derived immunogenic proteins, 51 or proprietary costimulatory mixtures. 52,53 In one study of naturally occurring plant polysaccharides used in ancient Chinese medicine, intraperitoneal injections of extracts from Antrodia cinnamomea were shown to enhance DC activation in vivo, with increased T H 1 T cells as well as increased native CD11c C DC's in tumor draining lymph nodes.…”
Section: Adjuvant For DC Vaccinesmentioning
confidence: 99%